Carbon Stock in Integrated Field Laboratory Faculty of Agriculture University of Lampung - Irwan Sukri Banuwa; Tika Mutiasari; Henrie Buchori; Muhajir Utomo (UNIVERSITY OF LAMPUNG, 2016)
This study aimed to determine the amount of carbon stock and CO2 plant uptake in the Integrated Field Laboratory (IFL) Faculty of Agriculture University of Lampung. The research was conducted from April to November 2015. The study was arranged in a completely randomized block design (CRBD), consisting of five land units as treatment with four replications for each treatment. Biomass of woody plants was estimated using allometric equation, biomass of understorey plants was estimated using plant dry weight equation, and organic C content in plants and soils were analyzed using a Walkey and Black method. The results showed that land unit consisting of densely woody plants significantly affects total biomass of woody plants, organic C content in woody plants and total carbon content (above and below ground). The highest amount of woody plant biomass was observed in land unit 5, i.e. 1,196.88 Mg ha-1, and above ground total carbon was 437.19 Mg ha-1. IFL Faculty of Agriculture University of Lampung has a total carbon stock of 2,051.90 Mg and capacity to take up total CO2 of 6,656.88 Mg.